2007
DOI: 10.1116/1.2803723
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy control at substrates during plasma etching of patterned structures

Abstract: Influence of ion mixing on the energy dependence of the ion-assisted chemical etch rate in reactive plasmasIn fluorocarbon-based plasma etching of dielectrics, deposition of fluorocarbon on the substrate contributes to a complex surface chemical structure that strongly affects etch rate and etch selectivity. Results reported herein demonstrate that the energy distribution of bombarding ions ͑IED͒ has a significant effect on this polymer layer, subsequently affecting etch rate and selectivity in submicron patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…External bias voltages are typically applied to the substrate to manipulate the ion energy distribution during processing [1]. It has been shown that adequate biasing of the substrate can significantly support the etch selectivity in semiconductor processing [2][3][4] or the synthesis of certain crystalline phases in the deposition of hard coatings [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…External bias voltages are typically applied to the substrate to manipulate the ion energy distribution during processing [1]. It has been shown that adequate biasing of the substrate can significantly support the etch selectivity in semiconductor processing [2][3][4] or the synthesis of certain crystalline phases in the deposition of hard coatings [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…21 ͑The angle of the IEAD is respect to the normal to the wafer.͒ One method to control the ion energies incident on the wafer is using a nonsinusoidal bias waveform to narrow the spread in energy. [22][23][24][25] It has been demonstrated that selectivity can be significantly improved using a narrow ͑in energy͒ IEAD as afforded by nonsinusoidal waveforms where the average ion energy is tuned to a value between the threshold energies of the two materials. One strategy for PALE would be to employ nonsinusoidal biases to discriminate between the threshold energies during the passivation and etch steps, thereby possibly eliminating the need for different gas mixtures ͑and so eliminate the purge step͒.…”
Section: Introductionmentioning
confidence: 99%
“…Since a limitation of these approaches with respect to throughput is the existence of purge steps, Agarwal and Kushner 9 also examined the question if elimination of the purge steps is possible and self-limited etching can be achieved if the entire SiO 2 etching cycle is performed using a single gas mixture, and simply controlling ion bombardment energies during a cycle by changing RF bias. By utilizing a nonsinusoidal bias waveform, 96,97 they controlled ion energy distribution functions, and demonstrated self-limiting etching at 1 to several ML/cycle. This method is related to pulsed plasma approaches.…”
Section: Iii-v: Gaasmentioning
confidence: 99%